Strategy for Implementing Agile Governance in Creating an Integrity Zone in the Rindam XIV/Hasanuddin Unit - Aji Mimbarno; Umanto Umanto (Asian Journal of Social and Humanities, 2024)
This research aims to develop a strategy for implementing Agile Governance as an effective approach in realizing an Integrity Zone in the Rindam XIV/Hasanuddin Unit. The main focus of the research is to analyze how Agile Governance principles can be integrated in the context of military organizations. By using qualitative research methods, the research results show that the application of Agile Governance contributes to efforts to achieve the Integrity Zone in the Rindam XIV/Hasanuddin Unit. Nonetheless, some challenges emerged, such as resistance to cultural change and the need to cope with the complexity of military duties. Recommendations are given in the form of: strengthening training and socialization, improving communication between units, and optimizing organizational adaptability in facing change. Ultimately, this research is expected to provide valuable insights for stakeholders in the military sector and contribute to the understanding of the application of Agile Governance in the context of bureaucratic reform.